2019
DOI: 10.1177/2473011419862228
|View full text |Cite
|
Sign up to set email alerts
|

Intense Therapeutic Ultrasound for Pain Relief in the Treatment for Chronic Plantar Fasciopathy

Abstract: Background: Intense therapeutic ultrasound (ITU) is an innovative ultrasound-based therapy where sound waves are concentrated into select musculoskeletal tissue. These focused waves generate thermal coagula at a controlled depth and space while preserving surrounding tissues. A multicenter study was conducted evaluating the efficiency, safety, and patient tolerance of ITU for the treatment of chronic plantar fasciitis (CPF) pain. Methods: Seventy-four CPF patients, having failed conservative and/or minimally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In comparison with baseline, the treatment group reported a substantial decrease in average pain (-26%, -33%, -43%) and hypoechoic lesion volume (-33%, -53%, -68%) at weeks 4, 8, and 12. Treating patients reported significantly more daily living activities (+28%, +42%, +47%, +40%) compared to the sham/control group (+0.12%, +12%, +3%, +21%) [21]. However, in terms of pain reduction and functional improvement, a meta-analysis comprising five RCTs found that ESWT is superior to therapeutic ultrasound (MD = −1.36, P = 0.005) [22].…”
Section: Ultrasoundmentioning
confidence: 97%
“…In comparison with baseline, the treatment group reported a substantial decrease in average pain (-26%, -33%, -43%) and hypoechoic lesion volume (-33%, -53%, -68%) at weeks 4, 8, and 12. Treating patients reported significantly more daily living activities (+28%, +42%, +47%, +40%) compared to the sham/control group (+0.12%, +12%, +3%, +21%) [21]. However, in terms of pain reduction and functional improvement, a meta-analysis comprising five RCTs found that ESWT is superior to therapeutic ultrasound (MD = −1.36, P = 0.005) [22].…”
Section: Ultrasoundmentioning
confidence: 97%
“…An RCT compared therapeutic ultrasound to sham ultrasound and found that therapeutic ultrasound was no more effective than the sham group,[ 34 ] while another RCT showed the treated group had significant pain reduction compared to the sham group. [ 35 ] Another RCT found no additional benefit of therapeutic ultrasound when added to stretching exercise in treating PF. [ 36 ] When compared to ESWT, a meta-analysis incorporating 5 RCTs concluded that ESWT is superior to therapeutic ultrasound in pain reduction and functional improvement.…”
Section: T Reatmentmentioning
confidence: 99%
“…4 It is approved by the FDA for nonoperative brow lifts and has been demonstrated to produce a greater and more rapid reduction in heel pain and perifascial lesion size when compared to sham control. 45…”
Section: Minimally Invasive Treatmentsmentioning
confidence: 99%